Sistem Pakar Untuk Mendeteksi Kerusakan Pada Diesel Pump Dengan Metode Forward Chaining Berbasis Web - Haryadi, Haryadi; Yulia, Yulia (Department of Informatics, Siliwangi University, Indonesia, 2021)
Frequent fires can occur in or like buildings of buildings or high rise buildings. The losses incurred by the fire disaster are enormous. Care and maintenance standards for diesel engine pumps must be observed. All technicians must have expertise in the maintenance and maintenance of the diesel pump engine. Such expertise can be obtained from official training conducted by the education center, reading guidelines for dealing with diesel pump engine damage obtained from diesel pump manufacturing plants and additional knowledge gained from learning while attending education and training. In this study the researchers set